2021
DOI: 10.3390/su14010334
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Potential Impacts of Future Climate Change on Post-Rainy Season Sorghum Yields in India

Abstract: Given the wide use of the multi-climate model mean (MMM) for impact assessment studies, this work examines the fidelity of Coupled Model Intercomparison Project Phase 5 (CMIP5) in simulating the features of Indian summer monsoons as well as the post-rainy seasons for assessing the possible impacts of climate change on post-rainy season sorghum crop yields across India. The MMM simulations captured the spatial patterns and annual cycles of rainfall and surface air temperatures. However, bias was observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Changing Tmax and Tmin had an overall positive effect on sorghum yield, as evidenced by the improvement in sorghum yield for every 1°C increase in SE-US temperature (Table 6). This was also con rmed by Adejuwon [108] , Boomiraj et al [109] , Msongaleli et al [110] , Bosire [111] , and Chadalavada et al [112] . It is worth noting that, as per Prasad et al [100] , and Sunoj et al [113] regarding sorghum, temperatures greater than 32°C (the cutoff point) begin to negatively affect the RUBISCO mechanism, hampering photosynthesizing performance and, eventually, yield.…”
Section: Impact Of Climate Change During 41-yr Period (1980 To 2020) ...supporting
confidence: 71%
See 1 more Smart Citation
“…Changing Tmax and Tmin had an overall positive effect on sorghum yield, as evidenced by the improvement in sorghum yield for every 1°C increase in SE-US temperature (Table 6). This was also con rmed by Adejuwon [108] , Boomiraj et al [109] , Msongaleli et al [110] , Bosire [111] , and Chadalavada et al [112] . It is worth noting that, as per Prasad et al [100] , and Sunoj et al [113] regarding sorghum, temperatures greater than 32°C (the cutoff point) begin to negatively affect the RUBISCO mechanism, hampering photosynthesizing performance and, eventually, yield.…”
Section: Impact Of Climate Change During 41-yr Period (1980 To 2020) ...supporting
confidence: 71%
“…Further examination indicated that the total impact of marginal shift patterns in Tmax and Tmin was bene cial to sorghum yield, which may be inferred statistically as a net 1°C upsurge in overall temperature ameliorated sorghum yield (by 6%). Adejuwon [108] , Msongaleli et al [110] , Bosire [111] , and Chadalavada et al [112] also found similar results in terms of the positive effects of overall temperature-increasing patterns on sorghum. Recently, Mumo et al [120] estimated that yield increases due to temperature changes in the future could reach up to 80.7% in the case of sorghum (2050 to 2070), based on the current rate of temperature warming.…”
Section: Marginal Impact Of Climate Change (1980 To 2020) On Oats And...mentioning
confidence: 68%
“…The primary goal of the NEX-GDDP developers and distributors is to assist the science community in conducting studies of climate change impacts at local to regional scales. Subsequently, it is used for many applications around the globe as an assessment of the Indian summer monsoon [41,59,60] and as general investigations on near-and long-term climate projections over China [61] and Southeast Asia [35]. The overall conclusion is that the NEX-GDDP product offers considerable improvements over CMIP5 GCM hindcasts and projections at regional-to-local scales, with an unchanged global long-term increment [61].…”
Section: Datamentioning
confidence: 99%
“…Nevertheless, we selected suitable metrics to evaluate the NEX-GDDP MME MX50, namely the root mean square error (RMSE) and the index of agreement (IA) [66]. These statistics are applied in several studies evaluating and utilizing the NEX-GDDP dataset [41,59,60,67]. The IA is defined as follows:…”
Section: Present Climate Evaluationmentioning
confidence: 99%
“…Sorghum (Sorghum bicolor L. Moench) is known for its good adaptability to sub-optimal lands due to its tolerance to drought [2], aluminum toxicity [3], and inundation [4,5]. Additionally, sorghum cultivation and seed production techniques are more manageable than those of corn.…”
Section: Introductionmentioning
confidence: 99%